The neutrophil-to-lymphocyte and monocyte-to-lymphocyte ratios are independently associated with clinical outcomes of viral encephalitis - Qiang He; Qiang He; Qiang He; Shuo Wang; Haoan Chen; Lili Long; Lili Long; Lili Long; Bo Xiao; Bo Xiao; Bo Xiao; Kai Hu; et al. (Frontiers in Neurology, 2023)
BackgroundThe neutrophil-to-lymphocyte ratio (NLR) and monocyte-to-lymphocyte ratio (MLR) are used as prognostic biomarkers for many diseases. In this study, we aimed to explore the possibility of using ratios of NLR and MLR to predict the prognosis of viral encephalitis (VE).MethodsA total of 81 patients with an initial diagnosis of VE who were admitted to our hospital from January 2018 to January 2021 were retrospectively analyzed. A routine blood test within 24 h of admission was utilized to determine the ratios of NLR and MLR for each patient. The modified Rankin Scale (mRS) at 12 months after discharge was used to evaluate patients' clinical prognosis and the patients were divided into the group of good prognosis (mRS ≤ 1) and the group of poor prognosis (mRS ≥ 2) according to the mRS scores. Univariate and multivariable regression analyses were used to differentiate and assess independent prognostic factors for the prognosis of VE.ResultsNeutrophil-to-lymphocyte ratio and MLR of the poor prognosis group were significantly higher than that of the good prognosis group. Multivariate logistic regression analysis results showed that NLR [odds ratio (OR): 1.421, 95% confidence interval (CI): 1.105–1.827; P < 0.05] and MLR (OR: 50.423, 95% CI: 2.708–939.001; P < 0.05) were independent risk factors for the poor prognosis of VE. NLR > 4.32 and MLR > 0.44 were suggested as the cutoff threshold for the prediction of the poor prognosis of VE.ConclusionNeutrophil-to-lymphocyte ratio and MLR obtained from blood tests done at hospital admission have the potential to predict poor prognosis in patients with VE.